1990
DOI: 10.1007/bf00400202
|View full text |Cite
|
Sign up to set email alerts
|

Myo-inositol and prostaglandins reverse the glucose inhibition of neural tube fusion in cultured mouse embryos

Abstract: Neural tube defects in infants of diabetic mothers constitute an important and frequent cause of neonatal mortality/morbidity and long-term chronic handicaps. The mechanism by which normal neural tube fusion occurs is not known. The failure of rostral neural tube fusion seen in mouse embryos incubated in the presence of excess-D-glucose can be significantly prevented by the supplementation of myo-inositol to the culture medium. This protective effect of myo-inositol is reversed by indomethacin, an inhibitor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 36 publications
2
87
0
Order By: Relevance
“…The major products of lipid peroxidation, the hydroperoxides, are known stimulants of prostaglandin biosynthesis but inhibit the production of prostacyclin [54], an imbalance which may have deleterious effects on the embryo. The previous findings of a beneficial effect of arachidonic acid [33,34], prostaglandin E~ and F2c~ and prostacyclin [39] on embryos in a diabetic environment may also relate to this notion, since the supplementation of these substances may correct a possible imbalance in prostaglandin biosynthesis. Likewise, the finding of a beneficial effect of myo-inositol supplementation to high-glucose culture [39,40], compensating for a decreased embryonic uptake of this hexose [41], may be explained by a restored production of phosphatidylinositol and a subsequent normalization of phospholipase A2 activity [55].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The major products of lipid peroxidation, the hydroperoxides, are known stimulants of prostaglandin biosynthesis but inhibit the production of prostacyclin [54], an imbalance which may have deleterious effects on the embryo. The previous findings of a beneficial effect of arachidonic acid [33,34], prostaglandin E~ and F2c~ and prostacyclin [39] on embryos in a diabetic environment may also relate to this notion, since the supplementation of these substances may correct a possible imbalance in prostaglandin biosynthesis. Likewise, the finding of a beneficial effect of myo-inositol supplementation to high-glucose culture [39,40], compensating for a decreased embryonic uptake of this hexose [41], may be explained by a restored production of phosphatidylinositol and a subsequent normalization of phospholipase A2 activity [55].…”
Section: Discussionmentioning
confidence: 90%
“…Thus, both a high concentration of glucose [9], a low glucose concentration [31] and a high concentration of [3-hydroxybutyrate [32] have been shown to be teratogenic in vitro. Furthermore, various consequences of increased ambient glucose concentration have been suggested to play a role in the disturbed embryogenesis, such as arachidonic acid depletion [33,34], hyperaccumulation of sorbitol [35][36][37][38], deficiency of myo-inositol [36,37,[39][40][41] or alterations in trace metal concentrations of the offspring [42,43]. Mannose [44,45] and somatomedin inhibitors from serum of diabetic rats [46] also cause embryonic malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Preventive strategies have been examined in laboratory animals based on knowledge of these pathways, in attempts to reduce diabetic embryopathy associated with high glucose levels. For example, birth defect incidence has been reduced in diabetic mice by dietary supplementation with myoinositol (Baker et al, 1990), arachidonic acid (Goldman et al, 1985;Pinter et al, 1986), lipoic acid (Wiznitzer et al, 1999), or antioxidants including vitamin E (Sivan et al, 1996) and vitamin C (Siman and Eriksson, 1997). Torchinsky et al (1997) stimulated uterine immune cells in pregnant mice in an attempt to reduce fetal resorptions associated with diabetes, and made the unexpected observation of significantly reduced malformed fetuses.…”
Section: Maxillary Lengthmentioning
confidence: 99%
“…Maternal diabetes in rats and mice has shown impaired embryonic growth at the pre-implantation stage [12] While other diabetesrelated factors such as triglycerides and branched amino acid chains may influence the outcome of pregnancy [13], it has been suggested that the primary teratogen in diabetic pregnancy is hyperglycemia [14][15][16][17]. A number of teratological pathways in embryonic tissue have been identified, including variations in metabolism of inositol, arachidonic acid and reactive oxygen species (ROS) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%